Calculation of Higher Education Institution’s facilities and services applying the Life Cycle Costing approach contributing sustainability - Wafa, Wafaurahman; Sharaai, Amir Hamzah; Matthew, Nitanan Koshy; Akhundzada, Noor Ahmad (Hapres Limited, 2025)
Life cycle costing (LCC) estimates the total cost of a product or service over its entire life cycle. However, studies assessing LCC in higher education institutions (HEIs) are scarce. The purpose of this study is to calculate the total cost of an HEI. This study applies the LCC method to calculate the costs associated with Kabul University and the services it provides based on the cost inventory data for the 2020 reference year. The costs are categorized into various domains and components, including land and property, water, energy, maintenance, and operational costs. The results reveal that property costs constitute the largest portion, accounting for 75.69% of the university’s overall costs. The second most significant cost category is operational costs, contributing to 20.14%. The remaining costs, namely energy (0.38%), maintenance (0.34%), construction (0.29%), and water (0.15%) costs, collectively account for the remaining costs. Furthermore, the study found that energy, water, maintenance, and construction costs contribute significantly for 4–6 years of graduating students. However, there is no consensus on the appropriate discount rate for LCC calculations. This study examines different discount rates of 20%, 40%, and 50% to determine the net present value. Based on the findings, Kabul University’s costs are highly sensitive to variations in discount rates. In conclusion, this research establishes the cost per function unit (one student) for graduation periods of four, five, and six years at Kabul University to be 792,277.4232 AFs approximately USD 11,173.74, followed by AFs 660,231.186 (USD 9311.45), and AFs 528,184.9488 (USD 7449.16) respectively. These findings provide valuable insights for the higher education sector in effectively managing and planning their financial resources.